2004
DOI: 10.1097/01.hjh.0000125415.50839.7b
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of the polymorphism T1128C in the signal peptide of neuropeptide Y in a Swedish hypertensive population

Abstract: The present study indicates that the NPY T1128C polymorphism is an independent predictor for myocardial infarction and stroke in a Swedish hypertensive population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
2
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
3
35
2
2
Order By: Relevance
“…Wallerstedt et al [9] further extend the previously reported association of the NPY T1128C polymorphism with increased cardiovascular risks in Swedish hypertensive patients with myocardial infarction and/or stroke. Their study is significant because it was based exclusively on a prospect study cohort with a large sample size (1032 hypertensive patients), including 174 patients with myocardial infarction, 170 patients with stroke and 688 matched hypertensive patients.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Wallerstedt et al [9] further extend the previously reported association of the NPY T1128C polymorphism with increased cardiovascular risks in Swedish hypertensive patients with myocardial infarction and/or stroke. Their study is significant because it was based exclusively on a prospect study cohort with a large sample size (1032 hypertensive patients), including 174 patients with myocardial infarction, 170 patients with stroke and 688 matched hypertensive patients.…”
supporting
confidence: 63%
“…Because of its potential effects on cardiovascular and blood pressure regulation [1,4,5,7], the association between NPY gene polymorphism and cardiovascular diseases has been the focus of several studies in animals and humans. Although the study by Wallerstedt et al [9] was not the first attempt to identify an association between the NPY T1128C polymorphism and cardiovascular risks, their findings are the first to link the T1128C polymorphism to myocardial infarction and/or stroke in a hypertensive population. The human NPY gene was first cloned in 1986 [10] and was assigned to chromosome 7 pter-q22 [11] or chromosome 7p15.1 [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Furthermore, the NPY T1128C polymorphism has been reported to be associated with myocardial infarction and stroke in Swedish hypertensive patients. 26 This last study did not demonstrate an association of the Pro7 allele with common cardiovascular phenotypes such as BP, total cholesterol, low-density lipoprotein and high-density lipoprotein. However, in total, these studies suggest that the NPY T1128C polymorphism is a strong independent risk factor for various cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 68%
“…27 To date, most, if not all, positive associations reported with the NPY gene polymorphism T1128C have been found largely in the Netherlands and some Nordic countries such as Finland and Sweden. 15,25,26 Irreproducibility of positive findings has been a common criticism levelled at association studies investigating the common genetic basis of complex diseases. 22 The frequency of the Pro7 allele has been reported to be 0.08 in Finns, 0.03 in Dutchmen 17 and virtually absent in Japanese 28,29 and Koreans.…”
Section: Discussionmentioning
confidence: 99%